1974
DOI: 10.1161/01.res.34.2.251
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the Coronary Blood Flow across the Canine Heart Wall during Systole

Abstract: The transmural distribution of left coronary blood flow during systole was studied by measuring the myocardial uptake of a bolus of M Rb introduced into the coronary circulation when the perfusion was limited to the periods of systole. The measurement revealed a transmural gradient of systolic blood flow with a flow rate in the outer fourth of the left ventricle about twice that in the inner fourth. A gradient of flow encompassing all depths of myocardial tissue revealed that intramyocardial pressure during sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
4

Year Published

1975
1975
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(39 citation statements)
references
References 24 publications
1
34
0
4
Order By: Relevance
“…In our recent study, we observed that increased RVP in newborn infants with critical pulmonary stenosis severely restricts RCA flow (37). The extravascular compression factor of total coronary resistance has been estimated as 29% of total coronary vascular resistance (38). The decrease in ventricular pressure leads to a decrease in the intramural tension.…”
Section: Discussionmentioning
confidence: 98%
“…In our recent study, we observed that increased RVP in newborn infants with critical pulmonary stenosis severely restricts RCA flow (37). The extravascular compression factor of total coronary resistance has been estimated as 29% of total coronary vascular resistance (38). The decrease in ventricular pressure leads to a decrease in the intramural tension.…”
Section: Discussionmentioning
confidence: 98%
“…This finding is consistent with differences in the left and right coronary artery phasic flow patterns. 17 Intramyocardial pressure in the left ventricle is sufficiently high to impede flow to subendocardium during systole, 18 so most left coronary flow occurs during diastole." With left coronary dilation in the presence of hypotension, the transmural gradient of vascular tone required to compensate for subendocardial underperfusion during systole is compromised, and ischemia becomes more severe in subendocardial tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it is likely that increased impedance to subendocardial blood flow during systole contributed to the decrease in ENDO/EPI ratio during severe pulmonary artery occlusion (Walston et al, 1978;Monroe et al, 1972). Myocardial blood flow during systole is principally determined by the dynamic interaction of perfusion pressure, vasomotor tone, and intramyocardial presure (Downey and Kirk, 1974;Hess and Bache, 1976;Hess and Bache, 1979;Bellamy and Lowensohn, 1980). Unlike the left ventricle, during normal intraventricular pressures, right coronary artery blood flow occurs equally throughout the cardiac cycle (Lowensohn et al, 1976).…”
Section: Discussionmentioning
confidence: 99%